Tradisi Tedhak Siten dalam Perspektif Sosial dan Pendidikan Islam - Umro'atin, Yuli; Supriyanti, Iin; A’yun, Neny Qurrota (Jurnal Penelitian, 2023)
AbstractThis research was conducted using a descriptive qualitative approach, which explored empirical data in the field and was described in an in-depth descriptive manner. Data mining techniques with interviews, observation and documentation. The data analysis process goes through three stages, namely data condensation, data presentation and conclusions. The purpose to describe the history of the emergence of the tedhak siten tradition for the people of the city of Madiun, the implementation of the tedhak siten tradition for the people Madiun city, and the value of Islamic education from the tedhak siten tradition for the people of the city of Madiun. Results of the study: The history of the emergence of the tedhak siten tradition has long been before Islam came to the land of Java, then developed and preserved by Muslims until now to become a tradition of Javanese Islamic society which is characterized by religious values and Islamic education; The implementation of the tedhak siten tradition, namely when the baby is 7 months old, is ready to develop by crawling and is practicing standing and walking, this tradition begins with the ritual of bathing the flowers, held up by its parents and the soles of its feet are stepped on to Javanese food in the form of jaddah, baby is raised to the toy ladder with the word education level on it, the last one is locked up in a chicken cage in which various kinds of toys, then the congregation prays together; The value of Islamic education in the tedhak siten tradition is that newborn babies grow and develop into children who will later receive teaching and knowledge in their later adulthood. childhood level, elementary, secondary to tertiary education, and a child is equipped with the mind and knowledge. AbstrakPenelitian ini menggunakan jenis kualitatif deskriptif. Teknik penggalian data dengan wawancara, observasi dan dokumentasi. Proses analisis data melalui tiga tahapan yaitu pemadatan data, penyajian data dan penarikan kesimpulan. Tujuan penelitian ini untuk mendeskripsikan sejarah munculnya tradisi tedhak siten bagi masyarakat kota Madiun, pelaksanaan tradisi tedhak siten, dan nilai pendidikan Islam dari tradisi tedhak siten bagi masyarakat kota Madiun. Hasil penelitian: Sejarah munculnya tradisi tedhak siten sudah jauh sebelum Islam datang ke tanah Jawa, kemudian berkembang dan dilestarikan oleh umat Islam hingga saat ini menjadi tradisi masyarakat Islam Jawa yang bercirikan nilai-nilai religi dan Pendidikan Agama Islam; Pelaksanaan tradisi tedhak siten yaitu pada saat bayi berumur 7 bulan sudah siap berkembang dengan merangkak dan sedang berlatih berdiri dan berjalan, tradisi ini diawali dengan ritual memandikan bunga, injak kaki ke makanan ketan jaddah, naik tangga mainan yang bertuliskan jenjang pendidikan, dan dikurung dalam kandang ayam dengan macam mainan, serta do’a bersama; Nilai pendidikan Islam dalam tradisi tedhak siten adalah agar bayi yang baru lahir tumbuh dan berkembang menjadi anak-anak yang kelak akan menerima pengajaran dan ilmu di usia dewasa nanti.